Training on Cow Manure Liquid Organic Fertilizer Processing and Application on Green Spinach Plants in Alue Ambang Village - Dewi Puji Lestari; Agustinur Agustinur; Larista Larista (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Alue Ambang is a village in Mukim Teunom, Teunom District, Aceh Jaya Regency, Aceh Province, Indonesia. Based on the results of a field survey, the soil condition in the village garden is sandy loam soil. Sandy loam soil is able to quickly absorb water but cannot receive nutrients for plants. So that this type of soil requires additional fertilization. One of the types of fertilizer offered is organic fertilizer in the form of liquid. Liquid organic fertilizer (POC) is produced from the decomposition of organic matter such as leaves and animal waste. The purpose of this service activity is to provide knowledge and innovation about the importance of converting livestock waste into liquid organic fertilizer and fertilization methods with correct and appropriate concentrations. This activity was carried out for 3 months, attended by 8 farmer cadres and 13 village development students. The method used is direct training and practice. The several stages in this activity are: (1) survey stage, (2) training, (3) POC manufacture, (4) POC application, (5) harvesting and (6) processing. The result of this service activity is that the cow dung POC and farmer cadres get an understanding of the importance of utilizing cow dung waste as a liquid organic fertilizer and how to use house yard land as an effort to fulfill family food in Alue Ambang Village.